Electrical properties of shadow-mask patterned organic thin film transistor fabricated on plastic substrate - Lee, JW; Kim, JM; Ju, BK; Kim, JK; Oh, MH; Jang, J (KOREAN PHYSICAL SOC, 2004)
We have fabricated pentacene thin-film transistors (TFTs) on plastic substrates with carrier field effect mobility of 0.12 cm(2)/Vs and I-ON/I-OFF current ratio larger than 10(4) by the shadow-mask process. Pentacene TFTs were fabricated on plastic substrates by e-beam deposited oxide material, which has good adhesion and electrical properties on plastic substrates, as the gate dielectric, thermally deposited gold (Au) for the source and drain contact, and thermally evaporated pentacene for the growth of active layer. The shadow-mask process will save manufacturing cost and protect plastic substrates including active materials from organic solvent. Furthermore, all films deposited at low temperature were involved in reproducible fabrication of pentacene TFTs on plastic substrates and were suitable for an easy process for flexible display.
Keywords: EVAPORATED PENTACENE; GATE INSULATORS; TEMPERATURE; STABILITY; GROWTH